Optimization of Financial Satisfaction: Stimulant from Financial Literation and Inclusion for Society : - Yuliani Yuliani; Taufik Taufik; Luk Luk Fuadah; Ima Andriyani (LPPM Universitas Terbuka, 2022)
Purpose - The study aims to develop a theoretical model of financial satisfaction and an empirical research model on literacy and inclusion. Primarily, it aims to analyze the concepts of financial attitude, behavior, and knowledge. Methodology - Data were obtained from individuals at Palembang City South Sumatera in between the ages of 20 and 55 who earned an income were included in this research. Furthermore, the Structural Equation Modeling (SEM) technique was used to obtain data of non-probability 142 respondents between May and July 2019. Findings - The results showed that financial attitude and knowledge have a significant positive effect on literacy, while financial behavior shows insignificant impact on literacy. Financial literacy has a significant positive effect on inclusion and satisfaction. Meanwhile, financial inclusion has no significant impact on satisfaction. Originality - This research develops an empirical model of financial satisfaction by examining in detail how individuals increase the availability of products and services, including the ease of access.